Non-ideal theory and the requirement of effective remedies - Olsen, Tore Vincents (Politica, 2026)
The article examines non-ideal theory as a distinct perspective within political theory and explores whether actors have a duty to choose effective means in the defense of their fundamental rights under non-ideal conditions. Drawing on the theory of militant democracy, it introduces the distinction between ideal and non-ideal theory and analyzes the normative challenges that arise when ideal norms and principles are not observed by all. The focus is on forward-looking non-ideal theories and demand for effective remedies, but the article also suggests that backward-looking, deontological concerns may justify actions that are ineffective. It argues for a principle stipulating that presumed effective actions should be prioritized until it is clear that they will not reach their effect. The article presents a nuanced understanding of moral responsibility, legitimate resistance, and the role of effectiveness in non-ideal political theory.